Seasonal monitoring of urban heat island using multi-temporal Landsat and MODIS images in Tehran. Issue 2 (3rd April 2019) - Bokaie, Mehdi; Shamsipour, Aliakbar; Khatibi, Padideh; Hosseini, Ali
ABSTRACT: This study aimed to investigate the relationship between seasonal changes in land surface temperature (LST) and various land use/land cover (LULC) classes in Tehran in 2010. For this purpose, urban heat island (UHI) cores were detected. The relationship between spatiotemporal variations of UHIs and the LULC classes was studied. The results showed that UHIs have different causes due to the type of LULC classes in the region. The average temperature of the five LULC classes in different seasons revealed full compliance of the spreading pattern of UHIs in the city with the type of LULC. Daytime and nighttime MODIS LST maps were prepared to verify the results. The daytime LST map also confirmed the compliance of the spatial pattern of UHIs with the types of LULC. The consequences from the nighttime LST map revealed the movement and conduction of main cores of heat islands towards the central and densely populated areas of the city, which could be expected to be due to the high absorption rate of heat during the day by unnatural materials and energy emissions at night.